O ensino superior de educação física em Goiás: história de uma instituição de ensino superior (1963-1990) - Silva, Fernanda Gonçalves (2023)
The present work is inserted in the line of History and Historiography of Education of the Postgraduate Program in Education at the Federal University of Uberlândia and aims to investigate the history of higher education in Physical Education in Goiás from 1963 to 1990 within the Escola Superior de Physical Education of Goiás ESEFEGO, its pioneering spirit and exclusivism of almost three decades as the only public higher education institution in Goiás in Physical Education. It was necessary to understand higher education in Brazil, to present and analyze the teaching of Physical Education in Goiás. As a methodology, documentary research was carried out using the theory of the French philosopher Paul Ricoeur (2007) about written memory, which helped in the objective of explaining the consolidation of ESEFFEGO through documents and records. Furthermore, to historically understand higher education in Brazil, as well as the emergence of universities and the public policies that permeated the changes and transformations of education in Brazil, authors such as Cunha (2007) and Sampaio (1991) were used. To present the history of higher education in Goiás and the institution ESEFFEGO as the pioneer in higher education in Physical Education in Goiás, being the only trainer since its creation in 1963 until 1990, we use Silva (2008), Silva and Ferreira (2015), Adorno (2008) and Cordeiro (2019). As the main objective, this work showed the pioneering spirit and exclusivity of ESEFFEGO, and as secondary objectives, the rules that governed the physical education course within the time frame were presented, in addition to militaristic education and hygienist education that were carried out at the time. The present study is located in the field of Education historiography, mapping findings from the area of Physical Education. We chose cultural history as a theoretical contribution, thus making it possible to crossreference sources. Furthermore, the thesis of this text consisted of analyzing the relevance of ESEFFEGO in the consolidation of Physical Education as higher education, presenting as a conclusion the importance of the existence of this institution, which provided the possibility of, currently, having several universities and colleges that offer this course in the state.